PREFERENSI KONSUMEN TERHADAP MEDIA SOSIAL DALAM MENCARI DAN MEMBELI PRODUK SECARA ONLINE - Dyah Titisari Anugraheni; Veronica Kusdiartini (Fakultas Ekonomi Universitas Pekalongan, 2019)
When consumers buy goods, they certainly go through the information search stages. Through the internet, it would be easier for consumers to find references. As a media that is frequently visited, social media can be one of the consumer's references. Several social media give information the products what consumer is going to buy. The purpose of this study is to get the best combination of attributes chosen by consumers in finding and buying goods using social media. This study uses Conjoint Analysis, which is one of the techniques in multivariate analysis that is used to understand how consumers prefer the value of a product by combining separate benefits that exist from each attribute of the product. From the research, it was found that the combination of chat feature, social media accounts have more than 1000 follower, safe shopping and easy search for the desired items were ranked first as the most considered combination by respondents.Keywords: Social Media, Consumers Preferences, Conjoint Analysis